MENINGKATKAN DISIPLIN DAN HASIL BELAJAR MATEMATIKA MELALUI METODE PROJECT BASED LEARNING PADA PESERTA DIDIK SEKOLAH DASAR - Putri Utami, Kustyaning Feby; Utami, Ratnasari Diah; Handayani, Dwi Ratna (Universitas Veteran Bangun Nusantara, 2025)
Based on the initial observations that have been carried out, problems were found in the form of low levels of discipline and student learning outcomes before integrating project-based learning. The purpose of the research action was carried out as an effort to improve the attitude of discipline and learning outcomes of mathematics on the material of blocks and cubes in grade IV students of SD Negeri Karangasem 4, Surakarta, totaling 26. The research was conducted over two cycles through a series of planning, action, observation, and reflection. Data collection techniques include observation and written tests. Data analysis is qualitative and quantitative. The results of the study showed that the overall level of discipline of students showed a percentage of 58%, after the first cycle was carried out there was an increase in the rate of 77%, then the second cycle again showed an increase in the percentage of 92%. The learning outcomes of students before the cycle were carried out by 23%, increased in the first cycle by 62%, and in the second cycle again increased to 92%. The average overall score of students was 85 with a completion percentage of 92% as many as 24 students completed the KKTP. The data shows that the implementation of project-based learning can improve discipline and learning outcomes of students.